If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -8 + -6x = 20 Reorder the terms: -8 + 8x + -6x = 20 Combine like terms: 8x + -6x = 2x -8 + 2x = 20 Solving -8 + 2x = 20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 2x = 20 + 8 Combine like terms: -8 + 8 = 0 0 + 2x = 20 + 8 2x = 20 + 8 Combine like terms: 20 + 8 = 28 2x = 28 Divide each side by '2'. x = 14 Simplifying x = 14
| x=x+32 | | 6(x+5)-6=48-2x | | 5y+8=-1 | | 6(x+5)-6=48 | | 5(x-9)=7(x-3) | | 7y^2-8y-7=0 | | 3(X+2)(2x-10)=0 | | 8x^2=26x+357 | | .81t^2+140=0 | | 4+(-3)2= | | (x+5)=(3x-1) | | -0.3-2.7=-4.1 | | B+8=2 | | 5(r+3)=4+2r+2 | | x-2.3=6.4 | | 750=y+(y*.07) | | 15-3x=7x+5 | | 6cos-1=2 | | 4(q)=52 | | 2(4x+1)=3x-9x | | 1996.43x=7385-67x | | R-(-5)=9 | | 8(4-n)+2=90 | | 44221=a*2+b | | 2(5x+7)+3=10x+17 | | 2x-17=2x-12 | | 3(r+7)=15 | | 4r-1=-4+4r+3 | | -4(x+9)=7-3x | | 2(4x-10)=46 | | 3m+3=5 | | -15+3=-2(x+7) |